2011
DOI: 10.1103/physrevc.84.064316
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of antiparallel proton and neutron angular momenta at low spins

Abstract: The meaning of the fact that the angular momenta of protons and neutrons are oriented in opposite directions, shown by Otsuka [Phys. Rev. Lett. 71, 1804(1993] for the angular-momentum-projected Nilsson wave functions, is reexamined using a two-rotor model. It is shown that this fact does not necessarily mean an unphysical situation that proton and neutron ellipsoids are rotating freely in opposite directions. On the contrary, it originates in a close binding of the two ellipsoids, which is accompanied by a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In Ref. [1], Otsuka and we have shown that the elimination of the spurious center-of-mass motion does not substantially change the situation in a classical treatment of independent nucleon motions. By using a simple two-rotor model in 2-dimensional space, we have also given a correct interpretation of the opposite-direction correlation of the two angular momenta, as is discussed in Sec.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…In Ref. [1], Otsuka and we have shown that the elimination of the spurious center-of-mass motion does not substantially change the situation in a classical treatment of independent nucleon motions. By using a simple two-rotor model in 2-dimensional space, we have also given a correct interpretation of the opposite-direction correlation of the two angular momenta, as is discussed in Sec.…”
Section: Introductionmentioning
confidence: 82%
“…JJ [2] is larger than θ (1) JJ (≈θ (2) JJ ) by ∼ 0.3 radians. However, the decreasing behavior is common to all the definitions.…”
mentioning
confidence: 84%
See 3 more Smart Citations